The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1954
DOI: 10.1002/zamm.19540340851
|View full text |Cite
|
Sign up to set email alerts
|

Über das Spektrum bei Eigenschwingungen ebener Laminarströmungen

Abstract: Die Stabilitätsuntersuchung einer Laminarströmung nach der Methode der kleinen Schwingungen führt mit einer gewöhnlichen. Differentialgleichung vierter Ordnung auf eine nicht selbstadjungierte Randwertaufgabe. Von den Eigenschwingungen dieser Randwertaufgabe hat man bisher vorwiegend die neutralen und angefachten betrachtet. In der vorliegenden Arbeit soll nun das gesamte Spektrum der Eigenwerte c sowie die Gestalt der Eigenschwingungen untersucht werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…In this alternate approach we first note that the solutions of equation ( The solutions have been normalized, following Grohne (1954), so that [cf. equation (3.16)]…”
Section: The Characteristic Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this alternate approach we first note that the solutions of equation ( The solutions have been normalized, following Grohne (1954), so that [cf. equation (3.16)]…”
Section: The Characteristic Equationmentioning
confidence: 99%
“…As Synge (1938) has remarked, "the deduction of general results from this equation is well-neigh impossible" and some further approximations must obviously be made. In his early work on this problem, Hopf (1914) [see also Grohne (1954)J considered three approximations which lead to an enormous simplification of the characteristic equation. First, he effectively approximated the Airy functions A k «( + C( 2 S2) by Ak(O; this is clearly permissible since, from equation (2.31), Ak(O is simply the first term in the uniform expansions of A k «( + C( 2 S2) for bounded values of 1' 11.…”
Section: The Characteristic Equationmentioning
confidence: 99%
“…The most famous and thoroughly studied approach, the spectral/modal approach (spectral expansion of disturbances in time and space, followed by the eigenfunction analysis), was derived by Orr. 1 A large collection of literature exists on the application of this approach to homogeneous incompressible [2][3][4][5][6] and compressible shear flows, [7][8][9] as well as inhomogeneous stratified or magnetized shear flows. [10][11][12][13][14] A comprehensive introduction to this field can be found, for instance, in the book by Schmid and Henningson.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies of the linear stability problem have been carried out by Grohne (1954), Gallagher andMercer (1962, 1964), Deardorff (1963), Davey (1973), and Gallagher (1974); however, all these studies found no evidence of instability. A number of analytic studies have also been carried out on this problem.…”
Section: Introductionmentioning
confidence: 99%